Free field Active Noise Control system development using a 3D Finite Element based approach - Budnik Maximilian; Mees Valentin (Acta Acustica)
This technical article presents a systematic methodology for efficient design, modeling, and validation of an Active Noise Control (ANC) system under free field conditions, aiming for global noise reduction. The presented three-dimensional (3D) Finite Element (FE) based simulation approach enables efficient ANC system design by generating valid data. It further allows for the optimization of control algorithms, evaluation of the attenuation performance, and methodical iteration of the overall concept design. A mock-up of a mobile ventilation system equipped with an ANC array serves as a demonstrator to present the stages of this methodology and its practicality. Starting with general concept considerations, the numerical modeling procedure, the different stages of verification and validation and concluding with an optimization task to achieve global noise reduction. The physical model of the demonstrator has been experimentally validated, and the efficiency of the developed ANC system confirmed through standardized sound power measurements in a semi-anechoic chamber. The findings reinforce the elaborated simulation process and demonstrate the real-world applicability of ANC systems. They also prove the potential for using simulations to develop free field 3D ANC systems capable of achieving global noise reduction.